Emissions and Efficiency Outcomes of Variable Rate Fertilizer Application: A Case Study of Canola Yield and Sustainability - Singh, Navdeep; Getigan, Clarissa; Gómez, Juan Marcelo (International Journal on Food, Agriculture and Natural Resources, 2025)
Agriculture contributes significantly to greenhouse gas emissions, mainly attributable to the ineffective and uniform application of fertilizers, seeds, pesticides, and irrigation water. Precision agriculture technologies, especially those utilizing variable rate input applications, provide an effective solution by modulating input quantities according to the distinct conditions of each field segment. While prior research has examined the theoretical advantages of these technologies, few empirical studies have measured environmental and agronomic effects across various input types. This study examines primary data from variable rate fertilizer application by quantifying the reductions in input utilization and corresponding scope three greenhouse gas emissions. The analysis contrasts traditional uniform application methods with precision-based strategies, demonstrating quantifiable advantages in reduced indirect emissions, enhanced input-use efficiency, and improved crop yield. The results encourage precision agriculture techniques by underscoring the environmental and productivity advantages of precision-managed inputs to guide agricultural policy, promote sustainable farming practices, and aid global warming mitigation efforts.